LEVERAGING INTELLECTUAL CAPITAL FOR SMALL AND MEDIUM ENTERPRISES (MSME) DIGITALIZATION IN PONTIANAK CITY - Reswari, Rianti Ardana; Yahya, Rizky Fakhrul; Dami, Dami (Fakultas Ekonomi dan Bisnis Universitas Tanjungpura, 2025)
Digital technology performs as a profound element to establish business sustainability. The Indonesian government is urging business to engage in the digital ecosystem; however, local business continue to face substantial challenges. Limited technological adoption has constrained the digital transformation of Micro, Small, and Medium Enterprises (MSMEs), despite their critical role in the national economy. As key components of organizational intellectual capital, individual knowledge and skills are essential for enabling technological innovation. Digital technologies can enhance marketing performance of MSMEs, yet effective adoption requires adequate digital literacy for a business. The research intended to examine the influence of intellectual capital possessed by human resources in adopting technological innovation and digital literacy on the business marketing performances. A quantitative approach was employed using the SmartPLS 4 through SEM-PLS methods with total of 130 data sets. The findings underscore the need to strengthen digital literacy capacity as a manifestation of individual knowledge and skills to support business development and advance MSMEs competitiveness. JEL: M21, M31, O33.